Female infertility – risk factors - Furqan, Saira; Sarah Saba Yasin,; Muhammad Saad,; Muhammad Salik, (Journal of the Pakistan Medical Association, 2025)
Female infertility is a complex health concern with a multitude of risk factors and aetiologies. This current narrative review was planned to highlight the various significant contributors to female infertility, including age-related decline in fertility, ovulatory dysfunctions, endometriosis, uterine abnormalities, pelvic and tubal adhesions, and lifestyle factors, such as smoking, alcohol consumption, caffeine intake, exercise, psychological stress and drug abuse. While advanced age and some medical conditions undeniably lower reproductive potential, modifiable lifestyle choices also play a vital role. Early diagnosis, prompt and appropriate management, and awareness of these factors are imperative for optimising fertility outcomes. Public health strategies should emphasise education and awareness of lifestyle choices that impact fertility, alongside advocating timely interventions for those at risk. There is a critical need for robust research to augment the present understanding of female infertility and its complex interplay with these factors. Key Words: Female infertility, Risk factors, Ovulatory disorders, Endometriosis, Lifestyle factors, Pelvic adhesions, Tubal blockage, Uterine abnormalities, Age-related decline, Nutrition and fertility.